Bacterial distribution and drug resistance in blood samples of children in Jiangxi Region, 2017–2021 - Zhou, Yan; Zhou, Shuping; Peng, Jun; Min, Liang; Chen, Qiang; Ke, Jiangwei (Frontiers in Cellular and Infection Microbiology, 2023)
Objective This study aims to investigate the distribution and drug resistance of bacteria in clinical blood culture specimens from children in Jiangxi province in recent years and to provide a foundation for preventing and treating bloodstream infection diseases in children. Methods The study involved a statistical analysis of the isolation and drug resistance of bacterial strains obtained from blood culture specimens of children in Jiangxi province between 2017 and 2021. The analysis was performed using the WHONET 5.6 software. Results A total of 7,977 bacterial strains were isolated from the blood samples of children between 2017 and 2021. Of these, 2,334 strains (29.3%) were identified as Gram-negative bacteria, and 5,643 strains (70.7%) were identified as Gram-positive bacteria. The most commonly isolated pathogens were coagulase-negative Staphylococcus, Escherichia coli, and Staphylococcus aureus. Among the Gram-negative bacteria, Escherichia coli (840 strains, 36.0%), Klebsiella pneumoniae (385 strains), Salmonella (283 strains), Acinetobacter baumannii (137 strains), and Pseudomonas aeruginosa (109 strains) were the most prevalent. Among the Gram-positive bacteria, coagulase-negative Staphylococcus (3,424 strains, 60.7%), Staphylococcus aureus (679 strains), Streptococcus pneumoniae (432 strains), Enterococcus sp. (292 strains), and Streptococcus agalactiae (192 strains) were the most common. Resistance to third-generation cephalosporins (cefotaxime/ceftriaxone) was observed in 45.9% and 56.0% of Escherichia coli and Klebsiella pneumoniae strains, respectively, while resistance to carbapenems was observed in 4.6% and 20.3% of these strains, respectively. Resistance to third-generation cephalosporins (cefotaxime/ceftriaxone) was observed in 15.5% of Salmonella strains, while resistance to imipenem was absent. Carbapenem resistance was observed in 17.1% (20/117) and 13% (14/108) of Acinetobacter baumannii and Pseudomonas aeruginosa strains, respectively. Methicillin-resistant Staphylococcus aureus (MRSA) was detected in 32.7% of the strains, while methicillin-resistant coagulase-negative Staphylococcus was detected in 64.3% of the coagulase-negative Staphylococcus strains. No Staphylococcus bacteria resistant to vancomycin were detected. Four strains of vancomycin-resistant Enterococcus faecium were detected over the 5-year period, and one strain of linezolid-resistant Enterococcus faecalis was detected. Conclusion Gram-positive cocci were the most commonly isolated clinical pathogens in blood specimens from children in Jiangxi province. The composition of the pathogen species showed a slight change over the years. The detection ratios of pathogens varied with age group and season. Although the isolation rate of common carbapenem-resistant Enterobacter bacteria has decreased, it remains high. It is necessary to monitor the antimicrobial resistance of pathogens causing bloodstream infections in children more closely, and antimicrobial agents should be used with caution.